Abandon statistical inference - Amrhein,Valentin; Trafimow,David; Greenland,Sander (PeerJ Preprints, 2018)
There is a massive crisis of confidence in statistical inference, which has largely been attributed to overemphasis on and abuse of hypothesis testing. Much of the abuse stems from failure to recognize that statistical tests not only test hypotheses, but countless assumptions and the entire environment in which research takes place. Unedited and unselected results must vary from replication to replication because of varying assumption violations and random variation; excessive agreement itself would suggest deeper problems, such as failure to publish results in conflict with group expectations or desires. Considerable non-replication is thus to be expected even with honest and complete reporting practices, and generalizations from single studies are rarely if ever warranted. Because of all the uncertain and unknown assumptions that underpin statistical inferences, we should treat inferential statistics as highly unstable local descriptions of relations between model predictions and data, rather than as generalizable inferences about hypotheses or models. And that means we should treat statistical results as being much more incomplete and uncertain than is currently the norm. Rather than focusing our study reports on uncertain conclusions, we should thus focus on describing accurately how the study was conducted, what problems occurred, and what analysis methods were used.
Keywords: NHST; Significance; Publication bias; Replicability; P-value; Descriptive statistics; Inferential statistics; Uncertainty; Reproducibility; Hypothesis testing